Environmental Impacts on Human Health - Qarashat Mohammad Shakir Ali Assaraj (Universitas Serambi Mekkah, 2022)
This paper discusses the environmental impact on human health through various concepts including Islamic thinking. Thus, the human environment relationship was defined from different perspectives; science, philosophy, and Al-Qur'an. The natural environment, human, and health were defined the same way. For more obvious description of the relationship between human and nature and its impact on people’s health, a comparison between the environmental factors affecting human health and the human activities impact on environment was carried out.Keywords: Environment, Human, Health.